Importance of the motivational climates of the other significatives on sport behaviours in Young athletes - F. M. Leo; T. García Calvo; P.A. Sánchez; F. R. Gómez; D. Sánchez (Asociación Española de Ciencias del Deporte, 2010)
The main aim of this study is to examine the interactive effects among motivational climates of the other significatives regarding sportsmanlike behaviour of youth athletes belonged to team sports, as well as assess the differences among the several categories of those participants. The sample is formed by 1070 male and female athletes affiliated in different team sports (basketball, handball, football and volleyball). The instruments assessed perceived motivational climate in peers, perceived motivational climate in coaches, parents` participation and sportsmanlike. The statistical techniques were descriptive analyses, reliability analysis, bivariate correlations, lineal regression analysis and analyses of variance. Results revealed a positively significant relationship between player's perception of mastery climate of the other significatives with respect to sportsmanlike behaviour, as well as performance climate of the other significatives regarding maladaptative behaviour. Finally, we highlight that promote a mastery climate can led to more sportsmanlike behaviour in players, as well as it will decrease maladpatative behaviour in the game.  Key Words:  sportpersonship, motivational climate, other significants, team sports.